Developing Bebras-Style Computational Thinking Test Instruments for English Learning in Elementary School - Mutiara Wahyu Daniella (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2025)
The test instrument development research aims to determine the computational thinking ability of students towards English language learning. The type of research used is R&D with the 6-Stage Borg and Gall development model (Research and Information Collecting, Planning, Initial Product Development, Expert Validation, Revision Expert Validation, Product Implementation). The test instrument that is suitable for use has passed the eligibility standard stage, namely, validity, reliability and difficulty level. The research was conducted at SD Negeri 105855 PTPN II Tanjung Morawa with class IV research subject totaling 35 studentrs. Data from validator result using Cohen’s kappa of 0.65 with strong category. In this study obtained 10 valid questions from 15 questions developed with a reliability value of 0.62 in the moderate category. Then the results of the student ability test show the average score of students 90.85 excellent category. The findings suggest that Bebras-style questions effectively measure the components of CT-decomposition, abstraction, pattern recognition, algorithmic thinking-and support meaningful English learning outcomes.